Catholic Anthropology from an Ecological Perspective: Pastoral Study in the Light of the Encyclical Laudato si’ - Przybyłowski, Jan Kazimierz (Collectanea Theologica, 2021)
One of the important causes of the ecological crisis is the egoistic mentality of contemporary people and the lack of respect for the natural order and immanent purpose of the creation. In order to shape a new pro-ecological consciousness a new concept of man and his relations with the environment is needed. One of the proposals is Catholic anthropology, whose ecological foundations were indicated by Pope Francis in his Encyclical Laudato si’. It is a proposal to describe man applying religious concepts, but also including the up-to-date knowledge about man and the environment. It is a concept open to dialogue, the aim of which should be the development of a pro-ecological lifestyle for contemporary people. Catholic anthropology postulates to combine “external” ecology with “moral” ecology, which can help modern man not only to have control over nature, but also to become its defender through small, everyday activities. In ecologically oriented anthropology, the created world is treated as a common home, and Pope Francis calls it our sister, with whom we share existence, and a beautiful mother, who takes us in her arms.